Social mapping of marginalized and vulnerable groups in urban informal settlements: a participatory action research approach - Chumo, Ivy; Kabaria, Caroline; Mberu, Blessing (Frontiers in Sustainable Cities, 2025)
The “leaving no one behind” principle of Sustainable Development Goals (SDGs) acknowledges inclusion of marginalized and vulnerable groups (MVGs) in all spheres. A methodological gap often hinders adequate execution, frequently lacking community engagement in prioritization of MVGs to facilitate inclusion. To bridge this gap, researchers employed a qualitative, two-pronged approach that involved social mapping and participatory focus group discussions (FGDs) in two informal settlements in Nairobi, Kenya. The study identified, characterized and ranked MVGs including persons with disabilities, child-headed households, older persons, and refugees. It also pinpointed three main root causes of their vulnerability and marginality: deferential (referring to status), economic/livelihood, and social factors. Key challenges faced by these groups included limited access to basic amenities, restricted political representation, unemployment and barriers to information access among others. Addressing challenges of MVGs requires a multi-pronged strategy that includes identifying and prioritizing these groups regularly and understanding the root causes of their marginalization. Regular social mapping and the active participation of MVGs are crucial for developing inclusive policies and programs to achieve social justice and wellbeing in line with the SDGs' “leaving no one behind” principle within the urbanization sector.